INDUSTRIAL DEVELOPMENT OF SIVAGANGA DISTRICT (International Journal of Psychosocial Rehabilitation, 2020)
In this paper the researcher explicates the industrial development of Sivaganga District. The Sivagangai district is an industrially in reverse district. It has eight industrial reverse squares. The interest for administrations expanded more than the interest for manufactured products. India needed to plan an economic policy according to the necessities of the changed worldwide markets. There are no social issues imagined because of the nonappearance of rural land or recovery as a result of hardly any different undertakings. Three SHGs per hinder in Dindigul, Pudukkottai, Ramanathapuram, and Sivagangai districts and four SHGs per obstruct in Thoothukkudi districts, with each gathering comprising 15 individuals, were recognized as recipients. No different squares aside from Sivagangai (285 people/post box) and Kannangudi (404 people/post box) squares adjust to the recommended standard of post enclosing office each town with a populace of more than 500.